TECHNOLOGICAL innovations - Business Source Premier (Business Source Premier, 2021)
Here are entered works on fundamental technological improvements or changes in materials, production methods, processes, organization, or management which increase efficiency and production. Works on original devices or processes are entered under "Inventions."
Keywords: Sciences économiques; Thésaurus de base de données

Social innovation - Business Source Premier (Business Source Premier Thesaurus, 2021)
Here are entered works on the mobilization of public and private resources to develop and support promising, innovative community-based solutions that impact social issues such as economic opportunity, healthy futures, and youth development. Broader Terms SOCIAL change Related Terms : INNOVATION management SOCIAL entrepreneurship
Ce terme permet de chercher tous les documents portant sur ce sujet qui sont recensés dans la base Business Source Premier.
Keywords: Sciences économiques; Thésaurus de base de données

Social innovation - EconLit (EconLit)
Dans la base EconLit, on ne peut chercher avec des sujets spécifiques comme "social innovation", les documents étant classés par grandes catégories. Le plus simple est de chercher "social innovation" en expression exacte dans le champ Abstract (Résumé)
Keywords: Sciences économiques; Thésaurus de base de données

Community-based programs - National Association of Social Workers (Social Work Abstracts)
Dans Social Work abstracts, le terme Social innovation est présent mais peu utilisé. Le terme "community-based programs" permet de trouver plus de documents.
http://opurl.bib.umontreal.ca:8331/V/P5M7MTANMHTJP8UAIV4LK7A9VYVM3VF2L86YU8KX9UGTUJUKCJ-02468?func=native-link&resource=MON06004
Keywords: Thésaurus de base de données; Travail social

Technology - Business Source Premier (Business Source Premier, 2021)
Here are entered general works on the application of technical knowledge to practical problems, including the development and study of machines, tools, and techniques of manufacturing and production methods and processes. Use only if a narrower term does not apply (e.g., "Educational technology" or "Technocracy"). Works on the technology used in particular wars are entered under the name of the war subdivided by – Technology, e.g., "World War, 1939-1945 – Technology." [EPC]
Keywords: Sciences économiques; Thésaurus de base de données

Social innovation - Business Source Premier (Business Source Premier Thesaurus)
Here are entered works on the mobilization of public and private resources to develop and support promising, innovative community-based solutions that impact social issues such as economic opportunity, healthy futures, and youth development. Broader Terms SOCIAL change Related Terms : INNOVATION management SOCIAL entrepreneurship
Ce terme permet de chercher tous les documents portant sur ce sujet qui sont recensés dans la base Business Source Premier.
Keywords: Sciences économiques; Thésaurus de base de données

TECHNOLOGICAL innovations - Business Source Premier (Business Source Premier)
Here are entered works on fundamental technological improvements or changes in materials, production methods, processes, organization, or management which increase efficiency and production. Works on original devices or processes are entered under "Inventions."
Keywords: Sciences économiques; Thésaurus de base de données

Technology - Business Source Premier (Business Source Premier)
Here are entered general works on the application of technical knowledge to practical problems, including the development and study of machines, tools, and techniques of manufacturing and production methods and processes. Use only if a narrower term does not apply (e.g., "Educational technology" or "Technocracy"). Works on the technology used in particular wars are entered under the name of the war subdivided by – Technology, e.g., "World War, 1939-1945 – Technology." [EPC]
Keywords: Sciences économiques; Thésaurus de base de données

Social innovation - EconLit (EconLit)
Dans la base EconLit, on ne peut chercher avec des sujets spécifiques comme "social innovation", les documents étant classés par grandes catégories. Le plus simple est de chercher "social innovation" en expression exacte dans le champ Abstract (Résumé)
Keywords: Sciences économiques; Thésaurus de base de données

Community-based programs - National Association of Social Workers (Social Work Abstracts)
Dans Social Work abstracts, le terme Social innovation est présent mais peu utilisé. Le terme "community-based programs" permet de trouver plus de documents.
http://opurl.bib.umontreal.ca:8331/V/P5M7MTANMHTJP8UAIV4LK7A9VYVM3VF2L86YU8KX9UGTUJUKCJ-02468?func=native-link&resource=MON06004
Keywords: Thésaurus de base de données; Travail social